ANALISIS IMPLEMENTASI PROGRAM MAKAN BERGIZI GRATIS DALAM MENUNJANG KEGIATAN PEMBELAJARAN DI SEKOLAH DASAR DI KOTA PALEMBANG - Ine Aprilia; Bukman Lian; Bambang Hermansah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The limited fulfillment of essential nutritional elements at a young age that risks disrupting learning concentration and daily motor development is the background of this research activity. These operational problems trigger physical lethargy, decreased focus, and weakened resilience of independent learning of students in the classroom. The main focus of this scientific study is to analyze the implementation of the Free Nutritional Meal Program (MBG) in supporting learning activities, its instructional impact, as well as operational obstacles and tactical solutions in the field. The steps of this descriptive qualitative research were operated using a multi-case study strategy in two elementary schools in Palembang City. Informant recruitment was carried out using a purposive sampling method involving fourteen active subjects including the principal, teachers, and fifth-grade students. The data collection procedure was collected through periodic observation techniques, semi-structured interviews, and documentation studies, which were then synthesized interactively through data reduction and presentation. Qualitative findings empirically revealed that the MBG program was implemented very well with the use of sterile stainless steel containers and had a positive impact on boosting physical fitness and learning motivation of students. Logistical obstacles in the form of distribution delays were overcome by adjusting the draft class schedule. The main conclusion confirms that a balanced diet has proven to be highly effective in supporting the development of students' disciplined character. Elementary education practitioners are recommended to consistently strengthen periodic governance coordination. ABSTRAK Keterbatasan pemenuhan unsur nutrisi esensial pada usia anak yang berisiko mengganggu konsentrasi belajar serta perkembangan motorik harian melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu timbulnya kelesuan fisik, penurunan fokus, serta melemahnya ketahanan belajar mandiri peserta didik di dalam kelas. Fokus utama kajian ilmiah ini adalah menganalisis implementasi Program Makan Bergizi Gratis (MBG) dalam menunjang kegiatan pembelajaran, dampak instruksionalnya, serta hambatan operasional dan solusi taktis di lapangan. Langkah-langkah penelitian kualitatif deskriptif ini dioperasikan menggunakan strategi studi multikasus di dua sekolah dasar Kota Palembang. Penarikan informan dijalankan menggunakan metode purposive sampling yang melibatkan empat belas subjek aktif meliputi kepala sekolah, guru, dan siswa kelas lima. Prosedur pengumpulan data dihimpun lewat teknik observasi berkala, wawancara semi-terstruktur, serta studi dokumentasi, yang selanjutnya disintesiskan secara interaktif melalui reduksi dan penyajian data. Temuan kualitatif secara empiris menyingkap bahwa program MBG terlaksana sangat baik dengan pemanfaatan wadah stainless steel steril serta berdampak positif mendongkrak kebugaran fisik dan motivasi belajar siswa. Hambatan logistik berupa keterlambatan distribusi diatasi melalui penyesuaian draf jadwal kelas. Simpulan utama menegaskan bahwa asupan pangan seimbang terbukti sangat andal menunjang pembentukan karakter disiplin siswa. Praktisi pendidikan dasar direkomendasikan memperkuat koordinasi tata kelola berkala secara konsisten.